Wolność w liberalizmie a prawda o wolności - Ślipko SJ, ks. Tadeusz (Annales. Etyka w Życiu Gospodarczym, 2008)
The freedom, in Latin libertas, is the object of philosophical reflection since Plato. Yet as the determined philosophical direction it took the form of the „liberalism” on the turning point of the sixteenth and seventeenth century, represented by two philosophers: Thomas Hobbes (1588–1679) and Jean-Jacques Rousseau (1712–1778). Among contemporary scholars Isaiah Berlin is standing out. From his point of view the philosophical problem of the freedom should be examined in two aspects: the negative freedom i.e. the attribute of not hindered freedom in making choices and the positive freedom as opportunity of being the master of one’s own fate. The author of the article, after critical demonstrating the conception of liberalism, sketches the theory of freedom from the position of Christian ethics. As a starting point he takes the conception of man as a person whose rational activities take on the form of twofold freedom of choice. In the psychological aspect, this freedom assumes the ambivalent form of doing good or evil, however in the moral aspect it turns out to be freedom put in order by the hierarchy of objective moral values. In this meaning the freedom also organizes the whole free man's activity and becomes creative strength of his moral personal perfection. It also defines the crucial sense of Christian philosophical science of truth about freedom.